Energy minimization methods in computer vision and pattern recognition 8th international conference, EMMCVPR 2011, St. Petersburg, Russia, July 25-27, 2011. proceedings - EMMCVPR 2011 (2011 Saint Petersburg, Russia); Boykov, Yuri.; Kahl, Fredrik; Lempitsky, Victor; Schmidt, Frank R.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 8th International Workshop on Energy Minimization Methods in Computer Vision and Pattern Recognition, EMMCVPR 2011, held in St. Petersburg, Russia in July, 2011. The book presents 30 revised full papers selected from a total of 52 submissions. The book is divided in sections on discrete and continous optimzation, segmentation, motion and video, learning and shape analysis.
Electronic reproduction.
Keywords: Computer vision -- Congresses .; Pattern recognition systems -- Congresses .; Electronic books